2010
DOI: 10.1177/0022002710383666
|View full text |Cite
|
Sign up to set email alerts
|

Does Globalization Breed Ethnic Discontent?

Abstract: This article examines how different components of globalization affect the death toll from internal armed conflict. Conventional wisdom once held that the severity of internal conflict would gradually decline with the spread of globalization, but fatalities still remain high. Moreover, leading theories of civil war sharply disagree about how different aspects of globalization might affect the severity of ethnic and nonethnic armed conflicts. Using arguments from a variety of social science perspectives on glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 73 publications
(101 reference statements)
2
50
1
Order By: Relevance
“…Such price fluctuations and unpredictability have led to food insecurity and conflicts. In a related area, Olzak (2011) observed that economic and cultural globalization are associated with deaths from internal armed ethnic conflicts, and that socio-cultural globalization increases ethnic conflicts, but reduces non-ethnic conflicts. By implication, globalization stimulates intra-ethnic competition for scarce resources, but it also creates a new understanding that diffuses interethnic frictions.…”
Section: Globalization and Peace And Stabilitymentioning
confidence: 99%
“…Such price fluctuations and unpredictability have led to food insecurity and conflicts. In a related area, Olzak (2011) observed that economic and cultural globalization are associated with deaths from internal armed ethnic conflicts, and that socio-cultural globalization increases ethnic conflicts, but reduces non-ethnic conflicts. By implication, globalization stimulates intra-ethnic competition for scarce resources, but it also creates a new understanding that diffuses interethnic frictions.…”
Section: Globalization and Peace And Stabilitymentioning
confidence: 99%
“…University] at 08:28 03 January 2015 1969), from a breakdown of institutions governing political representation (Olsen 1963), the dissonance between expectations and realities under new social orders (Gurr 1970), or economic globalization more generally (Olzak 2011). The centrality of major cities as centers of political and economic change suggests that this framework may also be relevant to understanding urban disorder and violence more generally.…”
Section: Downloaded By [Nova Southeasternmentioning
confidence: 99%
“…Additionally, if the abundant factor is concentrated in one particular group, anti-globalization hatred might be leveled against these pro teers of liberalization measures. The aforementioned studies by Chua (2003) and Olzak (2011) pay attention to the di erential impact that globalization might have across di erent ethnic groups. Their reasoning is, however, not solidly based on a political economy model that allows us to di erentiate between the income and redistributive e ects that liberalization has even for the less privileged group.…”
Section: Globalization Across Ethnic and Social Cleavagesmentioning
confidence: 99%
“…Glaeser (2005) develops a formal model of this argument suggesting that the incentive to spread hatred against such a globalizationpro teering minority grows because populists using this rhetoric have more to gain from asking for a redistribution of the integration bonanza. Only the study by Olzak (2011) has moved the empirical evidence in favor of such claims beyond the anecdotal illustrations by Chua (2003) and the descriptive evidence of Glaeser (2005). Distinguishing ethnic from non-ethnic wars and relying on fractionalization as a diversity measure, Olzak (2011: 21, italics suppressed) shows empirically that diversity intensi es the violence stemming from economic integration: "economic globalization actually raises the rate of fatalities from ethnic civil war."…”
mentioning
confidence: 99%
See 1 more Smart Citation